2012
DOI: 10.1111/j.1750-3841.2012.02898.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Hydroxytyrosol Rich Extract from Two‐Phase Chemlali Olive Pomace by Chemical Treatment

Abstract: The 2-phase Chemlali olive pomace is selected as substrate for chemical treatment. Treatment of "alperujo" using water bath or autoclave apparatus was carried out. A high amount of hydroxytyrosol was obtained using autoclave apparatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…Ghayth et al . [ 27 ] explored the possibility of obtaining HT in high yield from 2-phase Chemlali olive waste by an acid/alkaline chemical treatment. The results showed that a high amount of hydroxytyrosol (1360 mg/kg of fresh 2-phase olive pomace) was obtained using water bath after treatment at 80 °C for 90 min with 1 M of H 3 PO 4 , whereas the alkaline conditions (1085.8 mg/kg) were not very suitable.…”
Section: Resultsmentioning
confidence: 99%
“…Ghayth et al . [ 27 ] explored the possibility of obtaining HT in high yield from 2-phase Chemlali olive waste by an acid/alkaline chemical treatment. The results showed that a high amount of hydroxytyrosol (1360 mg/kg of fresh 2-phase olive pomace) was obtained using water bath after treatment at 80 °C for 90 min with 1 M of H 3 PO 4 , whereas the alkaline conditions (1085.8 mg/kg) were not very suitable.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, polyphenols have been investigated most by researchers, being involved in different processes. Hydroxytyrosol and tyrosol derivatives, iridoid precursors, seicoridoids and derivatives, flavonoids, lignans, and phenolic acids identified by different authors by means of liquid chromatography, 27,45,54‐60 which has also been coupled to tandem mass spectrometry using a quadrupole‐quadrupole‐time‐of‐flight (QqTOF) hybrid mass analyzer Among the phenolic acids, cinnamic, p ‐coumaric, caffeic, ferulic, and vanillic were detected 55 . The oleuropein derivatives were further identified among secoiridoids, flavonoids (i.e.…”
Section: Functional Compounds In Olive Pomacementioning
confidence: 99%
“…10). 52 In analogy to other lignin-like fragments discussed above (see the case of cardanol), 42 this and similar compounds would represent chemicals that are directly suitable for polyurethane chemistry. Analogous transformations could be considered for many families of compounds including tannins, 51 polyphenols widespread in the vegetal kingdom, or the well-studied triglycerides, the main component of vegetable oils.…”
Section: Lignin Derived Materials and Colloidsmentioning
confidence: 99%